Finding Kicking Range of Sepak Takraw Game: Fuzzy Logic and Dempster-Shafer Theory Approach - Andino Maseleno; Md. Mahmud Hasan; Muhammad Muslihudin; Tri Susilowati (Institute of Advanced Engineering and Science, 2016)
Sepak takraw is played by two regus, each consisting of three players. One of the three players shall be at the back and he is called a Tekong. The other two players shall be in front, one on the left and the other on the right. Having volley kicked a throw from the net by a team mate, the ball must then travel over the net to begin play. During the service, as soon as the Tekong kicks the ball, all the players are allowed to move about freely in their respective courts. The novel approach is the integration within a Tsukamoto's Fuzzy reasoning and inferences for evidential reasoning based on Dempster-Shafer theory. Sepak takraw is a highly complex net-barrier kicking sport that involves dazzling displays of quick reflexes, acrobatic twists, turns and swerves of the agile human body movement. Because of the human’s involvement in the game, the Fuzzy Logic type reasoning are the most appropriate. The individual rule outputs of Tsukamoto's Fuzzy reasoning scheme are crisp numbers, and therefore, the functional relationship between the input vector and the system output can be relatively easily identified. The result reveals that if Tekong is kick far and front player is kick near then another regu's player is kick far, if Tekong is kick near and front player is kick far then another regu's player is kick near, moreover possibility of kicking range is another regu's player is kick far in kicking range.